Successful Left Adrenalectomy for Metastatic Hepatocellular Carcinoma Using Hand-Assisted Laparoscopic Surgery : Report of a Case - Kitaoka, Fumio; Yanaga, Katsuhiko; Okudaira, Sadayuki; Tajima, Yoshimasa; Furui, Junichiro; Kanematsu, Takashi (Surgery today (Tokyo, Japan), 2005)
A 56-year-old man diagnosed a having multiple hepatocellular carcinoma (HCC) with liver cirrhosis underwent transcatheter arterial embolization (TAE). Five months later, recurrent HCC was detected in the liver as well as in the left adrenal gland. A second TAE was performed to treat the intrahepatic recurrence, which was followed by hand-assisted laparoscopic surgery (HALS) for the metastatic tumor in the left adrenal gland. The combination of the two procedures successfully controlled HCC. To our knowledge, this is the first report describing an adrenalectomy by HALS for adrenal metastasis from an HCC.